CFD simulation of horizontal oil-water flow with matched density and medium viscosity ratio in different flow regimes - Shi, Jing; Gourma, Mustapha; Yeung, Hoi (Elsevier, 2017)
Simulation of horizontal oil-water flow with matched density and medium viscosity ratio (μo/μw=18.8) in several different flow regimes (core annular flow, oil plugs/bubbles in water and dispersed flow) was performed with the CFD package FLUENT in this study. The volume of fluid (VOF) multiphase flow modeling method in conjunction with the SST k-ω scheme was applied to simulate the oil-water flow. The influences of the turbulence schemes and wall contact angles on the simulation results were investigated for a core annular flow (CAF) case. The SST k-ω turbulence scheme with turbulence damping at the interface gives better predictions than the standard k-ε and RNG k-ε models for the case under consideration. The flow regime of density-matched oil-water flow with medium viscosity ratio, or more generally speaking, the flow regime of fluids where the surface tension is playing a prevailing role is sensitive to the wall contact angle. Simulation results were compared with experimental counterparts. Satisfactory agreement in the prediction of flow patterns were obtained for CAF and oil plugs/bubbles in water. The simulation results also demonstrated some detailed flow characteristics of CAF with relatively low-viscosity oil (oil viscosity one order higher than the water viscosity in the present study compared to the extensively studied CAF with oil viscosity being two to three orders higher than the water viscosity). Different from the velocity profiles of high-viscosity oil CAF where there is sharp change in the velocity gradient at the phase interface with velocity across the oil core being roughly flat, there is no sharp change in the velocity gradient at the phase interface for CAF with relatively low-viscosity oil.
Keywords: Oil-water; Computational fluid dynamics (CFD); Volume of fluid (VOF); Flow pattern; Core annular flow (CAF)